Quality of Outpatient Care Services in a Private Hospital in Depok - Murniati, N (KnE Social Sciences, 2018)
Continuous quality improvement is an absolute target of private hospitals in order to retain customers and win the competition. Private hospitals should provide health care that reach all levels of society, and its management should be carried out on the principle of effectiveness and efficiency. This research reveals the public perception of service quality in the private hospitals in Depok. Research carried out a survey with a questionnaire to guide the interview. Subjects were the residents of Depok qualifying the inclusion criteria of using the service of private hospitals in Depok for a maximum of three months. Accidental sampling was conducted for one week. The hospital services had a limitation of only the outpatient installation. The survey was conducted in one-shot measurement in May 2014. The final result of the survey revealed that the reason for the respondents using the private hospital service in Depok was that it was close to home (50%), 25.5% said that the doctor was already subscribed and 10.0% went due to the recommendation. Furthermore, 66.3% of respondents felt that the service was fast and the waiting time was less, 90.9% of respondents felt that the medical examinations were sufficiently detailed, 93.6% of respondents felt that the nurses had a friendly attitude, 94.6% of respondents felt that the waiting room area was clean enough, and 86.4% respondents felt that the drug prices of the prescription were as expected. Keywords: outpatient care, private hospitals, quality of service